Study of the relationship between vitamin D deficiency, sunlight incidence and skeletal/extra skeletal diseases - Alice Barros Câmara; Igor Augusto Brandão (Universidade Estadual de Maringá, 2020)
It is estimated that more than 1 billion people worldwide have vitamin D insufficiency or deficiency. Vitamin D participates in bone mineralization, and is therefore important in osteoporosis, osteomalacia and rickets prevention. However, vitamin D deficiency could also be associated with several other pathologies. The present study aimed to investigate the relationships between vitamin D deficiency and vitamin D deficiency-related disorders in patients. In addition, this study aims to verify if countries with low solar incidence have higher extraskeletal disease death rates when compared to countries with high solar incidence. The vitamin D concentrations were obtained from the Heart Hospital database (Natal/Brazil). The relationship between solar incidence and death rate for vitamin D deficiency-related disorders was verified. Death rate data were extracted from the 'World Life Expectancy' repository and data about solar incidence were obtained from NASA's Surface Meteorology and Solar Energy project. These data were statistically processed with IBM SPSS v23.0 software and R programming language. Our results showed that patients with vitamin D insufficiency/deficiency showed significantly more bone diseases, thyroid diseases, hypercholesterolemy, hypertriglyceridemia, cancers, diabetes, hepatobiliary diseases, and urinary system diseases. Moreover, countries with high solar incidence have low cancer and multiple sclerosis death rates. This work suggests the participation of vitamin D and sunlight incidence in several diseases.